Buharlaşma Kayıplarının Yüzer Fotovoltaik Paneller İle Azaltılması - Korkmaz, Mehmet Seren (Fen Bilimleri Enstitüsü, 2015)
Türkiye'de serbest yüzey buharlaşma-terleme kayıpları, 274 milyar m3 olarak hesaplanmıştır. Bu rakam, ülkemizin yıllık kullanılabilir su potansiyeli olan 110 milyar m3 ün neredeyse 2.5 katıdır. Bitkilerden olan terleme (transpirasyon) ile ilgili kayıpların azaltılması teknolojik olarak mümkün olmasa da , buharlaşma(evaporation) kayıpları, toplam kaybın % 90'ını meydana getirdiğinden, bu kayıpların azaltılması hayati derecede önemlidir. Buharlaşma mekanizmasınıtetikleyen, hava sıcaklığındaki değişimlerdir. IPCC küresel iklim senaryolarında mevcut koşullar devam ederse 2070 yılı için ülkemizin yer aldığı orta enlem kuşağında beklenilen sıcaklık artışı 4-6 ºC'dir. Bu çalışmada, son 10 yıldır dünyada farklı coğrafyalarda kullanım alanı bulan yüzer tip fotovoltaik panellerle(YFP) buharlaşma kayıplarının azaltılması konusunda bir saha araştırması yapılmıştır. 2 adet Class A tipi Buharlaşma Tavası 20 cm derinliğinde su ile doldurulmuş, bir tanesinin üzerine (T-PV), yüzeyinin yarısını kaplayacak şekilde bir yüzer fotovoltaik panel platformu (YPFP) konulmuş, diğerininin (T-NPV) yüzeyi açık bırakılmıştır. Kurulan sistem, 30 gün boyunca serbest atmosfer koşullarında 2 tavadan meydana gelen buharlaşma kayıpları çeşitli hidrometeorolojik parametreler ile kıyaslanmıştır. Ayrıca Fotovoltaik Panelin (70 W Multikristal) ürettiği gerçek güç, özel tasarlanan bir devre ile ölçülmüş ve kaydedilmiştir. Serbest atmosferde üretilen güç değerleri ile üretici'nin laboratuardaki test verimlilik değerleri kıyaslanmıştır. Buharlaşma kayıplarına bakıldığında, (T-PV)'den 30 günde 38.7 mm buharlaşma olmuş, açık yüzeyli (T-NPV)'den 94.9 mm buharlaşma olmuştur. Buharlaşma miktarlarıarasındaki fark; 56.2 mm ve buharlaşma kaybındaki azalma %59.2 olarak tespit edilmiştir. PV'den üretilen ortalama güç 20.67 W olarak ölçülmüştür. Ardından beton bloklar üzerinde kurulu olan aynı niteliklere sahip bir diğer fotovoltaik panel platformu öncelikle kara(toprak) yüzeyde, ardından da su dolu buharlaşma tavasıüzerine oturtulmuş ve 5'er gün boyunca güç üretimleri ile ilgili, kara ve su yüzeylerindeki performansı incelenmiş sonuçlar karşılaştırılmıştır. Bunulan sonuçlara göre karayüzeyindeki PV'nin güç üretimi, su yüzeyindekine göre % 10.8 daha yüksektir. Bu da su üzerine kurulacak platformlarda PV Modülleri ile yüzey arasındaki ısı transferinin güç üretimine etkisinin olumsuz olduğunu göstermektedir. Son olarak yapılan çalışmada iki avadaki 3 defa su numunesi örnekleri mikrobiyolojik olarak analiz edilmiştir. Sonuçlar çarpıcıdır. (T-PV)'de ve (T-NPV) üreyen E.Coli miktarları sırası ile 9200 koloni/100 ml, 14000 koloni/100 ml, 12800 koloni/100 ml ve 400 koloni/100 ml, 120 koloni/100 ml, 2300 koloni/100 ml olarak belirlenmiştir. Bu da pratikte uygulanması halinde su kütlesi ekosistemi üzerinde bir baskı unsuru yaratmaması açısından kullanılan yüzer platform malzemesi içeriğinin önemli olduğunu göstermektedir.

Especially last 10 years, as parallel to increasing demand of energy, the most significiant improvements has been occured in Solar Energy Technologies if it is compared with other renewable energy technologies. In addition, as parallel to economic development, another increasing demand is about water supply. In the hydrological cycle, the biggest losses of water is evapotranspiration which is go back to the atmosfere as a form of water vapour. In Turkey, Evapotranspiration losses was calculated as 274 km3/year which is approximately 2.5 times bigger than annual available water potential of the country(110 km3/year). Unfortunately, there is no technological possibility to reduce transpiration losses which are sourced by plants during their grown up processes. But evaporation which is sourced from open water surface has a ratio of 90% of evapotranspiration losses. So, It is vitally important to reduce these evaporation losses. The mechanism of evaporation is drived by the change of air temperature. If the recent climate conditions would continue, the IPCC Global Climate Scenarios signs an increase between 4-6 °C over mid-latitudes in 2070. So, the reduce of losses from water resources and maximum benefits from the renewable energy of the country will have a role which is important to mitigate during a possible natural disaster as hydrometeorological drought. To Reduce of evaporation, there are many different type of solutions that some of them are physical solutions and some of them are chemical solutions. But every method have same approachment that is preventing of irradiance that come from sun. The Physical solutions like sun shading canvas have a significant economic cost. In addition, they haven't got any facility for money back. As well as physical solutions, chemical solutions have not guarantee to reduce loss of water. Because they vitally up to the instant weather conditions. For example, monomolecular layer which is one of chemical solutions have been applied over water surface, it can easily spread over water surface but if A heavy precipitation with strong winds occurs, it decreases the concentration of the chemical layer over water surface. So, the injection process have to be repeated again. Of course it affects the economic costs. In recent years there is a new method to reduce of evaporation from water storage areas. Floating PV Systems. Although the first purpose for using the method is to benefit the cooling effect of the water for behind PV's especially during hot daytime, the systems also close water surface and influence the mechanism of evaporation. In some countries like Australia which takes place in Tropical Climate Zone, applications of the method spreaded rapidly. Using of the method have a huge potential for innovative and enviromental technologies. Moreover, it depends on the most innovative renewable energy source which is Solar Energy. Financial cost of using solar energy have been decreased last 20 years. So, it is the fastest growing investment zone on energy marketing. Even if the investment cost seems to have disadvantages, in years, less operation and maintenance costs provide a remarkable decrease over this investments. This study is a field work about reduce of evaporation losses with using of floating PV Systems which are using in different geographical condition over the world in last 10 years. In this study, firstly two class A evaporation measurement pan have cleaned and prepared to operate for the field. The pans were fulled under a depht of reference level of 20 cm. Then a floating PV Platform was designed and constructed. For the platform, water wample bottles have been used as floating element. The bottles havee been mounted each other wit using a wooden layer. The wooden layer is also used to install PV. Total area of the platform is 0.57 m2 and Pans' surface area is 1.144 m2. So, the floating platform close half of a Pan. The Floating PV Platform was installed over one of the pans(T-PV). The second Pan has left as open surface (T-NPV). The evaporation losses over both of the pans were measured during 30 days between 11th of April and 11th day of May 2015. This time period was selected because of different weather conditions of spring season. The most challenging problem in the study is to measure and storage instant Power production of PV . Because of the electrical charactheristic of PV's, It is hard to measure power and then connect direclty to a data logger. A new designed special electrical circuit was used to solve this problem. The Circuit was reduce and adjust current and voltage load of PV for a multichannel 0-5000 mV differential voltage datalogger. An MPPT also was used to force PV to reach peak power. After 10 day usage, the Dataloogger's two channel (one for current and one for voltage) has been adjusted with some coefficients to show same values. So, the datalogger could show same value with what it was measured over a multimeter and what it is shown over the MPPT, as well. The results about the loss of evaporation shown that totally there is 38.7 mm of evaporation losses in 30 days from (T-PV). It has a volume of 44272.8 cm3. The average daily evaporation over (T-PV) is 1.29 mm/day. At the same time period, the evaporation amount of (T-NPV) is 94.9 mm. On this pan, the volume of evaporated water is 108565.6 cm3. The average daily evaporation over (T-NPV) is 3.16 mm/day. So, difference between covered and open surface is 56.2 mm in 30 days. The difference of the volume of evaporated water between two Pans is 64292.8 cm3. It equals to 59.2% of open surface water. The average power production of the Floating PV is 20.67 W. The maximum power production of PV is measured 58.2 W in 22nd of April at 03:40 p.m. The correlation coefficient between irradiance and PV Power production is determined as 0.849. The power production of PV stopped in night time and decreased in cloudy or rainy days. Besides, in the study, another PV that has same properties with the first PV has been established over concrete blocks which is not floated. This platform firstly seated over soil surface. After that, the platform seated over water surface which is one of the evaporation pans. Both of the situation of the platform have been operated for 5 days. Then the results of power productions of the PV have been compared. The results show that over soil surface, the power production performance of the PV is averagely 10.8% higher than over water surface's production. It means that heat fluxes from water surface has a negative effect over PV Power Production. Lastly, It was tested the situation of changing amount of mycrobacteria. Water samples show that the bacteria of E.Coli amount inside (T-PV) are 9200 colony/100 ml and 14000 colony/100 ml and 12800 colony/100 ml for (T-PV). The samples of the pan of (T-NPV) are 400 colony/100 ml and 120 colony/100 ml and 2300 colony/100 ml. So, inside of (T-PV) which is half-covered PV Platform, there is a significiant increase of E.Coli which indicates the importance of the choosing of the material about the negative impacts over the ecology of the water body. Because used floating platform has a potential risk for contain perfect conditions for bacterial growth. So, It is highly recommended that for floating platform material should be have an antibacterial and antifungal properties.
Reduce Of Evaporation Losses With Using Of Floating Photovoltaic Panels
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: buharlaşma; güneş enerjisi; yüzer fotovoltaik sistemler; evaporation; solar energy; floating PV systems